2015
DOI: 10.1111/jvec.12146
|View full text |Cite
|
Sign up to set email alerts
|

The effect of photoperiod on life history and blood-feeding activity inAedes albopictusandAedes aegypti(Diptera: Culicidae)

Abstract: Several studies have examined how climatic variables such as temperature and precipitation may affect life history traits in mosquitoes that are important to disease transmission. Despite its importance as a seasonal cue in nature, studies investigating the influence of photoperiod on such traits are relatively few. This study aims to investigate how photoperiod alters life history traits, survival, and blood-feeding activity in Aedes albopictus (Skuse) and Aedes aegypti (Linnaeus). We performed three experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 59 publications
(89 reference statements)
0
44
0
Order By: Relevance
“…Only the size of adult females was affected by photoperiod, and in contrast to the results described above from Yee et al (2012), Constanzo et al (2015) found that size increased rather than decreased under short day length conditions. The difference between the results of Costanzo et al (2015) and those of Yee et al (2012) is likely due at least in part to the different temperature conditions used in these experiments (25 C vs. 20 C). As noted above, photoperiodic effects can be highly temperature dependent (Pumpuni et al 1992, Bean et al 2012).…”
Section: Ae Albopictusmentioning
confidence: 82%
See 1 more Smart Citation
“…Only the size of adult females was affected by photoperiod, and in contrast to the results described above from Yee et al (2012), Constanzo et al (2015) found that size increased rather than decreased under short day length conditions. The difference between the results of Costanzo et al (2015) and those of Yee et al (2012) is likely due at least in part to the different temperature conditions used in these experiments (25 C vs. 20 C). As noted above, photoperiodic effects can be highly temperature dependent (Pumpuni et al 1992, Bean et al 2012).…”
Section: Ae Albopictusmentioning
confidence: 82%
“…The shorter larval development time under short-day conditions potentially indicated adaptive seasonal phenotypic plasticity to ensure maturation and successful reproduction before the onset of unfavorable winter conditions, with the sex-specificity of the response reflecting differences in the reproductive constraints of males versus females (Yee et al 2012). Costanzo et al (2015) used a population of Ae. albopictus from Florida to measure larval development time, adult female size, survival, life span, fecundity, and propensity to blood feed at 25 C under three photoperiod conditions-short day length (10:14, L:D), intermediate day length (12:12, L:D), and long day length (14:10, L:D).…”
Section: Ae Albopictusmentioning
confidence: 99%
“…Weekly meteorological data (maximum/minimum temperature, temperature range, accumulated rainfall, mean relative humidity, humidity range and mean vapor pressure of water) were calculated and used to data analysis. Besides, the photoperiod was added as variable, which has an effect on lifespan and blood feeding activity and controls the species survival [26]. Considering the biological characteristics of Ae.…”
Section: Methodsmentioning
confidence: 99%
“…DEET: air in one tube contained 4% CO2 and ticks were exposed to 50 ng鈥m -3 DEET. Significance of warm/cold or CO2/air difference: **: p<0.001; *: p<0.05. give increased host-seeking, feeding and longevity in studies with laboratory-reared adult Aedes albopictus and A. aegypti 13 .…”
Section: Other Supplementary Materials For This Manuscript Include Thmentioning
confidence: 99%
“…S3C) did not decline with increasing repellent concentration, indicating that repellents affect heat detection but not hostseeking behavior. We next examined the effect of DEET on the olfactory response to CO2, a necessary and sufficient stimulant of host-seeking behavior 6,13 . In control Y-tube bioassays testing medical grade air in both arms ( Fig.…”
mentioning
confidence: 99%